1996
DOI: 10.5326/15473317-32-2-131
|View full text |Cite
|
Sign up to set email alerts
|

Canine mucosal leishmaniasis

Abstract: Four dogs infected with Leishmania had proliferative lesions on the mucosae of the penis, tongue, oral cavity, prepuce, or nose. These mucosal, nodular lesions produced by parasites of the genus Leishmania have not been described previously in the dog. Leishmaniasis should be considered in the differential diagnosis of tumor-like lesions of mucous membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
1
40
1
2
Order By: Relevance
“…Dogs infected with L. infantum can present rare or atypical forms of leishmaniosis [4]. These include a few reported cases of single [5,6] or multiple tongue nodules [7,8] and ulcers of the lingual mucosa [4,9]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs infected with L. infantum can present rare or atypical forms of leishmaniosis [4]. These include a few reported cases of single [5,6] or multiple tongue nodules [7,8] and ulcers of the lingual mucosa [4,9]. …”
Section: Resultsmentioning
confidence: 99%
“…The first reference of tongue lesions in CanL was published by Font et al , who described a Leishmania -infected dog with proliferative lesions on the tongue and oral cavity mucosa [5]. Saari et al reported a 7-year-old male mongrel dog with a nodule protruding on the ventral surface of the tongue [6].…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory evidence of CKD can be present in approximately 50% of dogs with leishmaniasis. 4,5 Moreover, histopathologic evidence of nephropathy occurs in 100% of dogs with leishmaniasis. [6][7][8] Initially, infected dogs have moderate to severe proteinuria without azotemia.…”
mentioning
confidence: 99%
“…As glomerular disease progresses, tubulointerstitial lesions, azotemia, and ultimately, end-stage renal failure develop. 4,9 Early recognition of a kidney dysfunction allows appropriate therapeutics and, potentially, a better prognosis. Evaluation of kidney function at the early stages of CKD is complicated, because the techniques most commonly used in the clinical setting (blood urea nitrogen and serum creatinine [SCr] concentration) are useful only when a severe reduction of the renal functional mass has occured.…”
mentioning
confidence: 99%
“…Microscopic examination of the scarification specimens of the lesions showed the presence of protozoa, either free or included into the histiocytes. These lesions may be secondary to the first localization of the parasite in the organism (Font et al, 1996). Some authors have reported the presence of proliferative lesions as nodules or ulcers on the tongue mucosae, lower surface included, and on the oral and nasal cavities, caused by the action of the parasite (Lamothe, 1997).…”
Section: Introductionmentioning
confidence: 98%